Relative Level of Bacteriophage Multiplication in vitro or in Phyllosphere May Not Predict in planta Efficacy for Controlling Bacterial Leaf Spot on Tomato Caused by Xanthomonas perforans - Balogh, Botond; Nga, Nguyen Thi Thu; Jones, Jeffrey B. (Frontiers in Microbiology, 2018)
Following analysis of 8 phages under in vitro, growth chamber and greenhouse conditions with the bacterial spot of tomato pathogen Xanthomonas perforans, there was no correlation between disease control efficacy and in vitro phage multiplication, in vitro bacterial suppression, or in vivo phage multiplication in the presence of the host, but there was a low correlation between phage persistence on the leaf surface and disease control. Two of the 8 virulent phages (ФXv3-21 and ФXp06-02 ) were selected for in depth analysis with two Xanthomonas perforans (Xp06-2-1 and Xp17-12) strains. In in vitro experiments, phage ФXv3-21 was equally effective in infecting the two bacterial strains based on efficiency of plating (EOP). Phage ФXp06-02 , on the other hand, had a high EOP on strain Xp06-2-1 but a lower EOP on strain Xp17-12. In several growth chamber experiments, ФXv3-21 was less effective than phage ФXp06-02 in reducing disease caused by strain Xp06-2-1, but provided little or no disease control against strain Xp17-12. Interestingly, ФXp06-02 could multiply to significantly higher levels on the tomato leaf surface than phage ФXv3-21. The leaf surface appears to be important in terms of the ability of certain bacteriophages to multiply in the presence of the bacterial host. ФXv3-21, when applied to grapefruit leaves in combination with a bacterial host, was unable to multiply to high levels, whereas on tomato leaflets the phage multiplied exponentially. One plausible explanation is that the leaf surface may be an important factor for attachment of certain phages to their bacterial host.